1994
DOI: 10.1111/j.1365-2249.1994.tb06019.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating intercellular adhesion molecule-1 (ICAM-1) in autoimmune liver disease and evidence for the production of ICAM-1 by cytokine-stimulated human hepatocytes

Abstract: SUMMARY A circulating form of the membrane‐bound ICAM‐1 (CD54). a ligand for lymphocyte function‐associated antigen‐1 (LFA‐I), has recently been identified in normal human scrum. In this study. scrum levels of soluble ICAM‐1 (sICAM‐1) were determined by sandwich ELISA both in normal healthy individuals of both sexes and in subjects with autoimmune liver diseases. Patients with primary biliary cirrhosis (PBC). primary sclerosing cholangitis and chronic active hepatitis (autoimnune) showed significant elevations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 32 publications
3
16
2
Order By: Relevance
“…As reviewed by Kremer et al ., there are substantial restrictions for a clinical use of apoptotic markers in peripheral blood such as: (i) absent specificity; (ii) uncertain chronological decline of serum levels/activities; and (iii) competing pathomechanisms of cell death such as necrosis or necroptosis. Nevertheless, there have been attempts to establish apoptotic markers for clinical practice of immune‐mediated liver diseases …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As reviewed by Kremer et al ., there are substantial restrictions for a clinical use of apoptotic markers in peripheral blood such as: (i) absent specificity; (ii) uncertain chronological decline of serum levels/activities; and (iii) competing pathomechanisms of cell death such as necrosis or necroptosis. Nevertheless, there have been attempts to establish apoptotic markers for clinical practice of immune‐mediated liver diseases …”
Section: Discussionsupporting
confidence: 93%
“…In accordance with previous reports, the apoptotic markers sFas and sICAM (the latter in our study only in PSC) were elevated in sera of patients with immune‐mediated liver diseases when compared with healthy controls reflecting the higher rate of apoptosis under these pathological conditions. sICAM is the soluble form of the cell adhesion molecule ICAM (CD54), that seems to be involved in the pathogenesis of autoimmune hepatitis, and sFas is the soluble form of Fas (CD95), a receptor on the cell surface, that is an inducer of cellular apoptosis…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies reported increased sICAM-1 and sVCAM-1 values in patients with inflammatory diseases of the liver (34)(35)(36)(37)(38). While, elevated serum VCAM-1 in chronic hepatitis have been reported by some authors (39,40).…”
Section: Discussionmentioning
confidence: 87%
“…However, this study indicated that, in ALF patients, lower serum sICAM-1 levels were associated with their fatal outcomes. Part of sICAM-1 has been reported to be secreted from hepatocytes stimulated with pro-inflammatory cytokines such as IFN-γ, IL-1β and TNF-α [35]. After hepatic resection, serum sICAM-1 levels have been shown to decrease [36].…”
Section: Discussionmentioning
confidence: 99%